Co-inoculação de Rhizobium tropici e Azospirillum brasilense no feijoeiro-comum visando aumento de produtividade e redução de custo de produção - Souza, José Eduardo Barbosa de (2015)
SOUZA, J. E. B. Rhizobium tropici and Azospirillum brasilense Co-inoculation in common bean aiming at productivity increasing and costs reduction. 2015. 85 f. Dissertation (Masters in Agronomy: Soil and Water) – Escola de Agronomia, Universidade Federal de Goiás, Goiânia, 20151. The common bean (Phaseolus vulgaris L.) has great importance for the Brazilian population, contributing to about 20-28 % of the daily protein necessity. In the Midwest agricultural scenario, the common bean is present in different production systems, from those of low use of supplies to the high-performance and highly intensive technified systems. However, the production costs have been increasing, especially nitrogen fertilizers. An alternative for cost reducing is the bacteria capable of performing biological nitrogen fixation (BNF), associated with the plant growth promoter bacteria. The objective of this study was to evaluate the common bean agronomic and economic performance co-inoculated with Rhizobium tropici and Azospirillum brasilense. The experiments were conducted under field conditions for two consecutive years in the winter crop. The Pérola crop of common bean was subjected to the following treatments: T1-treatment control (without inoculation and fertilization); T2- nitrogen Witness with 20 kg ha-1 at planting and 60 kg ha-1 in the V2/V3 phenological stage; T3 Seed Inoculation with two doses of R. tropici (SEMIA 4080); T4 seed inoculation with two doses of R. tropici (SEMIA 4080) and another dose of A. brasilense (AbV-5); T5- seed inoculation with two doses of R. tropici (SEMIA 4080) two more doses of A. brasilense (AbV-5); T6- seed inoculation with two doses of R. tropici (SEMIA 4080), and pulverization of two doses of A. brasilense (AbV-5) in the V2/V3 phenological stage; T7- seed inoculation with two doses of R. tropici (SEMIA 4080) and the pulverization of three doses of A. brasilense (AbV-5) in the V2/V3 phenological stage. The treatments were arranged in randomized lineation blocks with four repetitions. In R6 phenological stage, nodulation and development parameters of the crop were evaluated. Data were submitted to variance analysis and the average compared by the Scott-Knott test at 5% probability. The T7 treatment provided a significant increase in the number of nodes, number of leaves, leaf area, dry weight of shoot and root parts, number of pods and number of grains and production related to the control treatment and among the done treatments in combination of R. tropici and A. brasilense the best performance. For the evaluation of the common bean crop production cost, it was used information from the Federation of Agriculture and Livestock of Goiás (FAEG) for the years 2013 and 2014. For the average of the four experiments, the seed inoculation treatment with two doses of R. Tropici and the pulverization after planting with three doses of V2/V3 phenological stage A. brasilense in the showed the average financial return of R$ 3,58 for every R$ 1,00 invested, that is, an increase of 358% on the investment, which is numerically higher than the average of the other treatments. The co-inoculation R. tropici and A. brasilense technology is an option for the producer for partial and / or total replacement of nitrogen chemical sources for the common bean crop.